The influence of knowledge, attitude, education and gender of the head of the family - RIANTI, Rima; WALOEJO, Christrijogo Sumartono; PUTRI, Anis Retno Indro; PANDIN, Moses Glorino Rumambo (Opción)
The study analyzes the influence of knowledge, attitude, education, and gender of the head of the family for household preparedness against a flood from the Bengawan Solo River in Kedungdowo Village, Balen District of Bojonegoro Regency. The research method used in this study is the survey method. This study is explanatory observational research. Data analysis methods used in this study are descriptive statistical analysis and logistic regression analysis with a 95% confidence level to identify the level of preparedness and the relationship between factors that affect preparedness. The findings show that knowledge, attitude, education, and gender significantly influence household preparedness.